The “Me and others” prevention program: impact evaluation in a sample of Portuguese adolescents - Alexandre, J. (Lisbon Addictions, 2024)
Non-substance addictions are an increasingly common disorder among young people, with significant negative impacts and where the statistics show very alarming results. Prevention is therefore essential. This study aims to 1) assess the extent to which narrative 9 of the ''Me and Others'' prevention programme run by the Addictive Behaviours and Dependencies Intervention Service (SICAD) promotes more beliefs about safe behaviour in the intervention group (IG) (vs. the comparison group/GC), and 2) which beliefs predict safer future behaviour. Following a pre- and post-test design (T1 and T2), with IG and CG, young people aged between 11 and 20 years took part in this study. The results obtained did not meet objective 1, i.e., there was no significant increase in beliefs about safe behaviour in the intervention group compared to the comparison group. It was also found (objective 2) that it is young people's attitudes that predict their future safe behaviour and not the subjective norm,considering the Theory of Planned Behaviour model. These results, on the one hand, reinforce the importance of evaluating and monitoring prevention programmes and, on the other, provide clues as to which variables can be considered in these programmes to promote saferbehaviours that seek to prevent substance dependence, and to plan longitudinal studies.